The incidence of COVID-19 in patients with metabolic syndrome and non-alcoholic steatohepatitis: A population-based study (2020)
Background The novel coronavirus disease (COVID-19) emerged from China in 2019 and rapidly spread worldwide. Patients with metabolic comorbid conditions are more susceptible to infection by COVID-19. Metabolic syndrome is a constellation of interlinked metabolic risk factors that predispose patients to increased risk of complications. Non-alcoholic fatty liver disease (NAFLD) is the hepatic manifestation of metabolic syndrome and non-alcoholic steatohepatitis (NASH) is the aggressive form of NAFLD.